Experimental study on mechanical and failure behavior of rock-concrete interface in coal mine roadway under direct tension - Weiyue Bao; Heping Xie; Tao Zhou; Dongya Han; Xiaoling Zhao; Jianbo Zhu (International Journal of Coal Science & Technology)
Abstract The rock-concrete interface has a significant influence on the stability of rock-concrete structures in coal mine roadway that are vulnerable to tensile loads. In this study, direct tension tests in combination with laser scanning and acoustic emission techniques were used to study the influences of loading angle and strength contrast on tensile behavior of rock-concrete interface. Results show that peak strain and tensile strength of granite-concrete specimens are lower than those of granite and concrete. Acoustic emission (AE) characteristic of the granite-concrete specimens differs from that of concrete and granite. With the loading angle increases, peak strain and tensile strength of the granite-concrete specimens increase, and the failure mode varies from the interfacial tensile failure to mixed tensile failure due to the increased contact area and decreased tensile stress applied on the granite-concrete interface. In addition, the accumulative AE counts of the granite-concrete specimen are also significantly affected by the loading angle; in particular, when the loading angle is sufficiently large, e.g., 55°, the accumulative AE counts sharply increase twice. Different strength contrasts between rock and concrete result in different failure characteristics of rock-concrete specimens under direct tensile loads. When tensile strength of rock is lower than that of concrete, failure often occurs in the rock section and the tensile strength and peak strain of the rock-concrete specimen is similar to that of rock. By contrast, when the tensile strength of rock is higher than of the concrete, failure appears at the interface, and rock-concrete interface dominates the tensile properties of rock-concrete specimens. The failure mode is dominated by the coupling effect of loading angle and strength contrast. The findings in this study are helpful in understanding the mechanical behaviour of rock-concrete structures under direct tension and applicable to the design and reinforcement of rock-concrete structures in coal roadway.